2017
DOI: 10.1136/lupus-2016-000173
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians approaches to management of background treatment in patients with SLE in clinical remission: results of an international observational survey

Abstract: BackgroundThe definition of remission in systemic lupus erythematosus (SLE) remains unclear, especially how background treatment should be interpreted.ObjectiveTo determine preferences of clinicians in treatment of patients in clinical remission from SLE and to assess how previous severity, duration of remission and serology influence changes in treatment.MethodsWe undertook an internet-based survey of clinicians managing patients with SLE. Case scenarios were constructed to reflect different remission states,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
0
25
0
2
Order By: Relevance
“…GCs tapering and withdrawal are considered one of the main targets of SLE management, but at present the decision of withdraw GCs is left to the judgement of the treating physician. A recent internet-based survey of 130 clinicians from 30 countries showed that preference of clinicians in treatment reduction in patients with SLE in clinical remission was variable with greater caution in treatment reduction when patients have persistent serological abnormalities and previous major organ involvement 5. Prednisolone was by far the first medication that physician suggested reducing or withdrawing during remission, irrespective of persistent serological abnormalities, remission duration, minor or major organ involvement and whether prednisolone was used with hydroxychloroquine (HCQ) alone or as part of a regimen also involving HCQ and an immunosuppressant 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCs tapering and withdrawal are considered one of the main targets of SLE management, but at present the decision of withdraw GCs is left to the judgement of the treating physician. A recent internet-based survey of 130 clinicians from 30 countries showed that preference of clinicians in treatment reduction in patients with SLE in clinical remission was variable with greater caution in treatment reduction when patients have persistent serological abnormalities and previous major organ involvement 5. Prednisolone was by far the first medication that physician suggested reducing or withdrawing during remission, irrespective of persistent serological abnormalities, remission duration, minor or major organ involvement and whether prednisolone was used with hydroxychloroquine (HCQ) alone or as part of a regimen also involving HCQ and an immunosuppressant 5.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids (GCs) play a central role in the treatment of active SLE but little data are available on GC withdrawal for patients once remission has been achieved 1–4. Although there is general agreement on the toxicity of GCs and the need to avoid long-term administration of these drugs, a significant proportion of treating physicians prefers to continue low-dose GCs despite clinical remission, particularly if there is a history of major organ involvement such as lupus nephritis or neuropsychiatric SLE 5. Observations of SLE cohorts reported that between 57% and 86% of patients undergo long-term low-dose GCs treatment 6 7…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey showed that clinicians’ preferences in withdrawing GCs in patients with SLE in clinical remission are highly variable: serological abnormalities, previous disease severity and duration of remission are the most recurrent variables that influence this decision 21…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent internet-based survey of 130 clinicians from 30 countries, a longer duration of clinical remission (>5 years) with normal serology is associated with approximately a 35% likelihood of GC withdrawal; however, a significant proportion of patients are kept on GCs by their treating physician despite clinical remission, particularly if there is a history of severe organ involvement. From the same survey, serology emerged as the main influencer for the physician’s decision to withdraw GCs 21…”
Section: Introductionmentioning
confidence: 99%
“…Действительно, наличие ремиссии или низкой активности является логичным основанием для решения вопроса о прекращении терапии ГК, принципиальное значение при этом имеет современная дефиниция состояния ремиссии СКВ [20]. Так, по данным опроса 130 клиницистов из 30 стран, длительная клиническая ремиссия СКВ (≥5 лет) и нормальные иммунологические показатели послужили основанием для отмены ГК у 35% больных [21]. В одном из последних исследований анализируется феномен отмены ГК у 91 из 148 пациентов в когорте СКВ, находившихся под наблюдением с 2012 по 2017 г.…”
unclassified